Gestión de Riesgo Operativo de la Florícola Agroganadera Espinosa Chiriboga S.A. - Murillo Vásquez, Adriana Elizabeth (2022)
The application of notions of operational risk management constitutes a process of analysis of the risk exposures that the company faces due to events derived from its internal processes, where the effective determination of financial risks is outlined as part of the initial premises that were considered to capture a model. Thus, the objective of this project is to develop an operational risk management proposal for Florícola Espinosa Chiriboga S.A. The approach was qualitative for events and for the interpretation of the information of the current situation from historical data, with deductive and inductive analysis for the objective and systematic description of the content. The techniques that were used to collect information were the documentary review and the semi-structured interview. The results presented gaps in risk management such as the insufficient capacity of financial personnel with weak intentions to recover the overdue portfolio according to the Accounts Receivable accounting account according to the variations from 2019 to 2020 with 24.64% and from 2020 to 2021. with 53.11%. The conclusions denoted that floriculture is sensitive to operational risks despite the strategic perspectives of regulation, control and monitoring, as well as practical recovery in the event that the financial risks detected that had a negative impact on internal processes, which are carried out carried out systematically.